A Psicologia na Atenção Básica à Saúde: uma relação dialógica com o SUS - Freire, Francisca Marina de Souza (2010)
Introduction: The insertion of psychologists in the Health Basic Attention services (HBA) is constant in spite of the fact that the literature still points deficiencies concerning the theory and practice of Psychology in this field of action. In this way, it was emerged the interest in verifying how the psychologists who work in ABS units of João Pessoa are learning and overcoming the challenges of this new practice in Psychology. Objective: To analyze the beliefs of psychologists living in João Pessoa/PB and working in HBA units. These beliefs are related to their practice in this context and related to the Public Health System. Method: About 20 psychologists participated of this study. This number comprised the population of psychologists who had worked in health primary institutions of the city, by the occasion of the study. The age range varied from 23 to 58 years old (M=44; SD=11, 8), being women the majority of the participants (17). In order to collect the data were used two instruments: Depth Interview and a Socio-labor Questionnaire. The instruments were analyzed, respectively, by the speech analysis technique and by descriptive statistics. Results: Significant differences related to function and work place of the participants led the analysis of data based on similarities and differences demonstrated between two groups of psychologists: a) the psychologists of UBS/USF and (b) the matrix supporter psychologists. The questions concerning the formation and professional service brought by the socio-labor questionnaire show that the groups are similar in relation to professional formation, which is focused on the clinic. The differences involved: a) complementary formation, especially focused on Collective Health, where the matrix supporter psychologists demonstrated more concern; b) the time of work in the context of health, which is superior to 10 years to the psychologists of UBS/USF, and c) working time and remuneration, which are superior to the matrix supporter psychologists. There are also similarities between the groups concerning the reasons which led them to work in the context of basic attention, where it was emphasized the reasons related to the identification with the work and labor insertion. In relation to the principles which rule the practice of these professionals, three thematic categories were highlighted: 1) the principles and guidelines of Public Health System; 2) personal values and 3) conceptions of health, being the first category more significant to the matrix supporter psychologists, whereas the two last categories are more significant to the psychologists of UBS/ESF. The groups are also similar referring to influenceable conditions related to the way of work in the ABS, where the condition which obtained more evidence and importance was the question related to the changes of experiences among the staff and professionals (f=16). According to the speeches of the participants, two thematic classes and five categories had emerged: 1) Thematic Class I The praxis of the psychologist in the ABS (Categories: insertion, practice and hole of the psychologist) and 2) Thematic Class II Health Public System (Categories: Conceptions concerning SUS and Whole Attention to Health). Conclusion: The differences and similarities which were realized between the groups of psychologists demonstrated that in spite of the fact that the psychological science still presents a deficient formation concerning the work in SUS and in the context of ABS, significant changes related to the conceptions of the youngest psychologists about their practice and this context have been realized.